To establish the prevalence of MTHFR C677T polymorphism in correlation with homocysteine metabolic markers in a black elderly community, in Sharpeville, Gauteng province in South Africa - Pule, Pule Bongani (Vaal University of Technology, 2021)
Background: Increased serum homocysteine is well known as an independent cardiovascular risk factor. Hyperhomocysteinemia may be due to several factors such as nutritional deficiencies and genetics. The MTHFR C677T polymorphism is associated with increased serum homocysteine. Folate and vitamin B12 play essential roles in lowering homocysteine levels. Limitations have been identified using serum vitamin B12 as a marker for vitamin B12 status due to lack an efficient of test. Holotranscobalamin has been reported as a more accurate marker for vitamin B12 status. Cardiovascular risk due to hyperhomocysteinemia has been confirmed among the elderly in Sharpeville. Knowledge of the prevalence of MTHFR C677T polymorphism among Black elderlies in South Africa is limited. Objectives: The main aim of the study was to evaluate the prevalence of MTHFR C677T polymorphism as a cardiovascular risk in an elderly black population in Sharpeville. Correlations between the presence of MTHFR C677T polymorphism and homocysteine metabolic markers were evaluated. Holotranscobalamin as a diagnostic test for vitamin B12 status was also assessed in this study. Materials and methods: This study was ethically approved by the Vaal University of Technology ethics committee (20140827-1ms). It was an observational, experimental study conducted in 102 elderly (≥60 years) attending the day-care centre in Sharpeville. Real-Time PCR was used to determine MTHFR genotypes. Folate and vitamin B12 were measured with AIA-PACK. Homocysteine levels were determined with an automated Konelab™ 20i and holotranscobalamin by ELISA. STATA 12 software was used for analysis of descriptive and inferential statistics. Results: The prevalence of MTHFR C677T polymorphism in this sample population was 19%. Heterozygous CT single nucleotide polymorphism was 17% and mutant homozygous TT was 2%. The majority (81%) of the subjects had wild type homozygous CC genotypes. No associations were found between MTHFR C677T genotypes and homocysteine and folate levels. Hyperhomocysteinemia was high (54%) and low (5%) folate deficiency found. No vitamin B12 deficiency was found however 7% were on the category of likely to be deficient. Sensitivity and specificity of holotranscobalamin were 100% and 95% respectively. Conclusion: The conclusions drawn from the study is that the prevalence of MTHFR C677T polymorphism is low within elderly in Sharpeville. There is a high risk of cardiovascular disease as a result of high prevalence of hyperhomocysteinemia. An intervention to lower homocysteine concentration of elderlies residing in Sharpeville is needed. Other genetic predisposing factors of increased homocysteine levels should be investigated.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: MTHFR C677T polymorphism; Cardiovascular risk; Hyperhomocysteinemia; Homocysteine metabolic; Holotranscobalamin; Polymorphism markers; Black elderly community; Homocysteine markers; Dissertations, Academic -- South Africa.; Cardiovascular system -- Diseases -- Risk factors.; Cardiovascular diseases in old age.; Genetic polymorphisms.; Older people -- Diseases.